2016
DOI: 10.1021/acs.iecr.6b03299
|View full text |Cite
|
Sign up to set email alerts
|

Silica Nanofluids in an Oilfield Polymer Polyacrylamide: Interfacial Properties, Wettability Alteration, and Applications for Chemical Enhanced Oil Recovery

Abstract: Oil production from matured crude oil reservoirs is still associated with low recovery factors. Chemical enhanced oil recovery (EOR) is one of the techniques which can significantly improve the recovery factor of the trapped oil. This is mainly achieved by lowering the interfacial tension (IFT) of the crude oil−brine/aqueous chemical and increasing the viscosity of the injected fluid. Nanofluids have demonstrated potential in this respect, and we thus examined how such nanofluids behave when formulated with st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
158
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(167 citation statements)
references
References 57 publications
9
158
0
Order By: Relevance
“…In comparing with the SiO2-PAM blend, PAM had significant stabilization effect at a concentration of 0.05 %. Similar observation of the particle stabilization with PAM was reported in the work of Sharma et al (2016), where the authors found that, SiO2 blend containing surfactant and PAM induced additional flocculation of particles, which resulted to rapid particles sedimentation. Thus, PAM in our study could only improve the viscosity of SiO2-IBS, but not its stability.…”
Section: Results Of Compatibility and Stability Studysupporting
confidence: 87%
See 1 more Smart Citation
“…In comparing with the SiO2-PAM blend, PAM had significant stabilization effect at a concentration of 0.05 %. Similar observation of the particle stabilization with PAM was reported in the work of Sharma et al (2016), where the authors found that, SiO2 blend containing surfactant and PAM induced additional flocculation of particles, which resulted to rapid particles sedimentation. Thus, PAM in our study could only improve the viscosity of SiO2-IBS, but not its stability.…”
Section: Results Of Compatibility and Stability Studysupporting
confidence: 87%
“…Despite high oil recovery achieved in FAWAG, obtaining stable foams in high temperature oil reservoirs are difficult and consequently affect their overall performance (Kapetas et al, 2016). However, silica nanofluid (SiO2), which is a recently employed technology, has been found to show a remarkable improve on the rheology, stability and interfacial properties of surfactants (Esmaeeli Azadgoleh et al, 2014;Sharma et al, 2016). The effects of SiO2 on stabilizing foams in different type of surfactants have been reported (Xue et al, 2016;Sun et al, 2015).…”
Section: *Enhancedmentioning
confidence: 99%
“…The efficiency of wettability change by silica NPs was shown to be enhanced at higher temperatures [20]. Apart from wettability change, silica NPs have also been shown to reduce oil-water interfacial tension thereby improving the mobility of oil phase [27][28][29] and stabilize oil in water emulsions [30][31][32][33] for EOR application. Monfared, et al [34] studied the adsorption of silica NPs on calcite surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Surfactants, whose amphiphilic structures enable the stabilization of emulsions with two immiscible phases, are widely applied in many processes such as cleaning [1], viscous oil transportation [2], and enhancing oil recovery [3]. Excellent stabilization is required in these processes, usually followed by a subsequent emulsion-destabilization step to effectively recover the two immiscible phases.…”
Section: Introductionmentioning
confidence: 99%